1999
DOI: 10.1177/0971890719990208
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Word of Mouth: An Empirical Investigation of Consumer Motivations

Abstract: The underlying purchase motives behind any purchase decision have always attracted the attention of researchers in the field of consumer psychology. The effect of word-of-mouth on consumers' purchase decision is one such area of interest which has remained under scruitinity of researchers for long. However, with significant changes in the socio-economic and sociocultural environment of Indian markets it has become imperative to look into the issue of word-of-mouth's effect on decision making afresh. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…A review of information sources used by consumers reveals that they collect information from a large number of sources like advertisements in television /radio/ magazines/ newspapers as depicted by Claxton et al, (1974); Duncan and Olshavsky (1982); Avery (1996); Moorthy et al, (1997); and Mishra et al, (1999). These studies also support the use of friends and family as a source of information.…”
Section: Literature Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…A review of information sources used by consumers reveals that they collect information from a large number of sources like advertisements in television /radio/ magazines/ newspapers as depicted by Claxton et al, (1974); Duncan and Olshavsky (1982); Avery (1996); Moorthy et al, (1997); and Mishra et al, (1999). These studies also support the use of friends and family as a source of information.…”
Section: Literature Reviewmentioning
confidence: 94%
“…These studies also support the use of friends and family as a source of information. Claxton et al, (1974); Moorthy et al, (1997); and Mishra et al, (1999) find that salesperson/retailer's advice is also considered while making buying decisions. Manufacturer's brochures and pamphlets is another source of information as depicted by Moorthy et al, (1997).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have also supported the use of friends and family. Claxton et al, (1974); Moorthy et al, (1997);and Mishra et al, (1999) found that salesperson/retailer's advice is also considered while taking buying decisions. Manufacturer's brochures and pamphlets is another source of information as depicted by Moorthy et al, (1997).…”
Section: Introduction :-mentioning
confidence: 99%
“…Manufacturer's brochures and pamphlets is another source of information as depicted by Moorthy et al, (1997). Past experience also updates the knowledge of consumers (Mishra et al, 1999). More recently the Internet has opened a vast number of opportunities for consumers to search for information (Nikolaeva and Sriram, 2006).…”
Section: Introduction :-mentioning
confidence: 99%